Ramadan Fasting Among Older Children and Adolescents With Type 1 Diabetes Mellitus: A Real-World Study From the UAE - Muammar, Tawfik; Fojas, Esphie Grace Fodra; Helal, Radwa; Lessan, Nader (Frontiers in Nutrition, 2022)
Background Ramadan fasting (RF) is a religious obligation for all healthy adult Muslims. The sick and pre-pubertal children are exempt, but many choose to fast for various reasons. In this “real world” study, glycaemic control has been investigated in the context of RF in children and adolescents with type 1 diabetes mellitus (T1DM) and compared multiple daily injections (MDI) and continuous subcutaneous insulin infusion (CSII) outcomes. Methods Children and adolescents with T1DM seen at Imperial College London Diabetes Centre who decided to fast in the ensuing Ramadan were educated with their families about diabetes mellitus management during RF using an adapted CHOICE (Carbohydrate, Insulin, and Collaborative Education) educational programme. Pertinent data including hypoglycaemia episodes and diabetic ketoacidosis (DKA) were obtained through patient/family interviews. Information on weight, glycated hemoglobin (HbA1c), and blood glucose levels from continuous glucose monitoring (CGM)/flash glucose monitoring (FGM) before (1 month prior), during, and after (1 month afterwards) Ramadan were retrieved retrospectively from the electronic database. Data are presented as mean ± SD. Results Forty-two patients [age 13.5 ± 2.4 years; 27 (64.3%) males; T1DM duration 4.9 ± 3.1 years] were included in the study and were able to fast for 22 ± 9 days during Ramadan. Twenty-three (54.8%) of the patients were on MDI and 19 (45.2%) were on CSII. No statistically significant differences were seen in CGM/FGM generated mean blood glucose level before, during, and after Ramadan [one-way ANOVA (F(2, 80) =1.600, p = 0.21)]. HbA1c and weight after Ramadan did not change significantly compared to baseline (paired t-test; p = 0.02 and p = 0.08, respectively). Between MDI and CSII groups, there was no significant difference in fasting days (p = 0.49), frequency of hypoglycaemia episodes (p = 0.98), DKA frequency (p = 0.37), HbA1c level (p = 0.24), and weight (p = 0.11) after Ramadan. Conclusion Data show no significant deterioration in indicators of overall glycaemic control which remained inadequate. RF should be discouraged in children with poorly controlled T1DM.